Simultaneous occurrence of inflammatory bowel disease and trichomonosis in a Maine coon cat - Santos, Cesar A. R. [UNESP]; Melo, Jessica C. [UNESP]; Sampaio, Leticia H. T. S. [UNESP]; Ferari, Lorena C. [UNESP]; Moura, Fernanda B. C. [UNESP]; Souza, Fulvia B. [UNESP]; Kobayashi, Priscila E. [UNESP]; Fonseca-Alves, Carlos E. [UNESP]; Okamoto, Priscylla T. C. G. [UNESP]; Rahal, Sheila C. [UNESP]; Melchert, Alessandra [UNESP] (Canadian Vet Med Assoc, 2022)
A 2-year-old, 4.2 kg, spayed female, Maine coon cat was referred to the veterinary hospital for evaluation of hyporexia, slow growth, and chronic, intermittent, mucoid, bloody, voluminous, and fetid diarrhea. The diarrhea had been observed since the cat was acquired from a cattery at 4 months of age; with acute worsening in the 5 d before presentation. Abdominal palpation revealed moderate pain. Ultrasonographic examination showed thickening of the jejunal wall and ileal loops, increased echogenicity of the jejunal mucosa, and enlargement of the jejunal and ileocolic lymph nodes. Histopathology of full-thickness intestinal biopsies showed moderate, diffuse, lymphoplasmacytic, erosive enteritis with hemorrhage and edema. Diffuse, lymphoplasmacytic, erosive colitis with mild, interstitial fibrosis and hemorrhage was also noted. The ileocecal lymph node biopsy showed eosinophilic lymphadenitis. Based on the immunohistochemical evaluation of intestinal samples with CD3 and CD79a antibodies, a diagnosis of lymphoma was ruled out. Fecal polymerase chain reaction testing was positive for Tritrichomonas foetus. Based on these results, inflammatory bowel disease and trichomonosis were diagnosed. Treatment for the cat included a hypoallergenic diet and an oral omega- 3 fatty acid supplement, in conjunction with prednisolone, to manage the inflammatory bowel disease. Ronidazole was administered to target the Tritrichomonas foetus. The cat was clinically normal during a follow-up examination after 6 months of treatment.